2022
DOI: 10.32604/cmc.2022.017698
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic Scheme for Concurrent Detection and Classification of Printed Circuit Board Defects

Abstract: An ideal printed circuit board (PCB) defect inspection system can detect defects and classify PCB defect types. Existing defect inspection technologies can identify defects but fail to classify all PCB defect types. This research thus proposes an algorithmic scheme that can detect and categorize all 14-known PCB defect types. In the proposed algorithmic scheme, fuzzy cmeans clustering is used for image segmentation via image subtraction prior to defect detection. Arithmetic and logic operations, the circle hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…These methods commonly use algorithms such as morphological methods, edge detection [14], Hough transform [15] and Fourier shape descriptors to describe the boundary characteristics of objects. Most existing PCB defect-detection methods achieve defect localization through subtraction or XOR operations [1,16] to find out the shape differences between two images. By analyzing PCB functional defects, we found that they can be further regarded as anomalies of the edge.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods commonly use algorithms such as morphological methods, edge detection [14], Hough transform [15] and Fourier shape descriptors to describe the boundary characteristics of objects. Most existing PCB defect-detection methods achieve defect localization through subtraction or XOR operations [1,16] to find out the shape differences between two images. By analyzing PCB functional defects, we found that they can be further regarded as anomalies of the edge.…”
Section: Related Workmentioning
confidence: 99%
“…A method proposed to locate defects by finding the differences between the barycenter-edge points distance sequences of the template and test image using the circular correlation theorem. However, it [1,16] relies too heavily on the centroid calculation which can be easily influenced by defect contour points, leading to defect-detection errors and poor anti-interference ability.…”
Section: Related Workmentioning
confidence: 99%
“…Regarding the traditional image-processing detection methods, Mukesh Kumar et al proposed a method to detect PCB bare board defects by combining image enhancement techniques and a standard template generation particle analysis [5]. Khlong Luang and Pathum Thani proposed a PCB defect classification method by using arithmetic and logical operations, a circular hough transform (CHT), morphological reconstruction (MR), and connected component labelling (CCL) [6]. Liu and Qu used a hybrid recognition method of mathematical morphology and pattern recognition to process PCB images and used an image aberration detection algorithm to mark images of PCB defects for defect identification [7].…”
Section: Introductionmentioning
confidence: 99%